Archaeological Expedition of the State Museum of the History of Religion in Eastern Crymea - Khrshanovskiy, Vladimir A. (Hyperboreus, 2006)
A survey of the excavations in Iluraton and Kytaia conducted by the expedition of the State Museum of the History of Religion.